2023
DOI: 10.1038/s41416-023-02237-7
|View full text |Cite
|
Sign up to set email alerts
|

MBTPS2 acts as a regulator of lipogenesis and cholesterol synthesis through SREBP signalling in prostate cancer

Abstract: Background Prostate cancer is the most common cancer in men in the developed world, with most deaths caused by advanced and metastatic disease which has no curative options. Here, we identified Mbtps2 alteration to be associated with metastatic disease in an unbiased in vivo screen and demonstrated its regulation of fatty acid and cholesterol metabolism. Methods The Sleeping Beauty transposon system was used to randomly alter gene expression in the PtenNul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…EIF2AK3 has been identified as an immune-related prognostic gene in breast cancer, exerting a role in tumor cell apoptosis and facilitating sustained protective antitumor immunity [ 28 ]. MBTPS2, a membrane-embedded zinc metalloprotease, activates signaling proteins involved in transcriptional control of sterol and the ER stress response [ 29 ], thus promoting the progression of prostate cancer [ 30 ] and colorectal cancer [ 30 ]. The RHBDD2 (Rhomboid domain containing 2) gene is found to be overexpressed in advanced stages of colorectal cancer (CRC) and potentially modulates the UPR pathway, thereby favoring cell migration, adhesion, and proliferation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…EIF2AK3 has been identified as an immune-related prognostic gene in breast cancer, exerting a role in tumor cell apoptosis and facilitating sustained protective antitumor immunity [ 28 ]. MBTPS2, a membrane-embedded zinc metalloprotease, activates signaling proteins involved in transcriptional control of sterol and the ER stress response [ 29 ], thus promoting the progression of prostate cancer [ 30 ] and colorectal cancer [ 30 ]. The RHBDD2 (Rhomboid domain containing 2) gene is found to be overexpressed in advanced stages of colorectal cancer (CRC) and potentially modulates the UPR pathway, thereby favoring cell migration, adhesion, and proliferation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Folding factors assist newly synthesized proteins in acquiring the correct three-dimensional fold, and a complex quality control system guarantees that only correctly folded proteins exit the ER. When misfolded proteins accumulate, the UPR is induced and ATF6 is activated after subsequent cleavage by S1P and S2P [76,77]. The activated ATF6 is released from the Golgi membrane and, upon transport into the nucleus, induces the expression of ER stress gene products [76,78].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have provided evidence that the decreases in S2P expression, and the absence of mature SREBP1 and ATF6 production, resulting in the failure to activate the UPR, can induce apoptosis in liposarcoma and prostate cancer cells [79,80]. A more recent study has found that the knockdown of MBTPS2 expression in human prostate cancer cells impaired cholesterol synthesis and uptake and reduced the expression of key regulators of fatty acid synthesis, FASN and ACACA, through SREBP signaling [77]. These data suggest that tumors driven in different key regulatory components of DNL and the UPR might respond dramatically to MBTPS2 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR was performed as described previously (3).Briefly, first-strand cDNA was produced by reverse transcription from extracted RNA samples using the High-Capacity cDNA Transcription kit (Applied Biosystems) following the manufacturers protocol. RTPCR was carried out using TaqMan Universal Master Mix (Thermo Fisher Scientific) with primer appropriate Universal ProbeLibrary probes (Roche).…”
Section: Real Time -Pcr (Rt-pcr)mentioning
confidence: 99%
“…Premature deaths from PC are a result of metastatic and/or recurrent disease for which there are no curative options. Building on our recent research on an in vivo Sleeping Beauty (SB) transposon based forward-mutagenesis screen (2,3), we explore putative role of ARID1A as a mechanism for progressive PC.…”
Section: Introductionmentioning
confidence: 99%